The Role of Risk Management and Internal Control in Improving Job Satisfaction: The Mediating Impact of Employee Performance PT. Putra Niaga Sejahtera Pangkalan Bun - Cipta, Hendra (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Research indicates that internal control and risk management enhance employee performance. This study aims to address two key questions: (1) How do risk management and internal control enhance employee performance at PT Putra Niaga Sejahtera Pangkalan Bun? (2) How does employee performance mediate the relationship between risk management, internal control, and job satisfaction at PT Putra Niaga Sejahtera Pangkalan Bun? The study adopts a quantitative methodology, employing a population survey targeting all employees of PT Putra Niaga Sejahtera Pangkalan Bun. Samples were gathered using a purposive sampling method. The questionnaire, designed to measure variables such as employee performance, job satisfaction, risk management, and internal control, was distributed to participants. The data were analyzed using statistical software like SmartPLS for mediation and multiple regression analysis. This research supports previous conclusions that effective risk management significantly improves employee performance. In addition, this study shows that effective internal control improves employee performance. This research also shows that risk management has a direct effect on job satisfaction; however, internal control may not affect job satisfaction directly, although other factors related to satisfaction may affect it. In addition, employee performance has no significant direct impact on job satisfaction and does not moderate the relationship between risk management and internal control.